REVITALISASI PENGELOLAAN DAN PENYELENGGARAAN TRI DHARMA PERGURUAN TINGGI DIANTARA PERSIMPANGAN KEPENTINGAN ANTAR BANGSA - Yohan Yohan (Sustainable, 2018)
At a recent time, a number of academics ranging from the ‘practical and theoretical academics,’ ‘political academicians,’ ‘academic politicians’ to ‘academic bureaucrats’ are encouragingly striving for responding to the demands of internationalization of Higher Education because of the pressure of global education interests. With the spirit of ‘education liberation’ relying on the General Agreement of Trade in Services (GATS) as a result of ‘industrial globalization matrix’ which is associated with economic motives initiated by the World Trade Organization (WTO) makes some developed countries enthusiastically promote their higher education institutions to a number of countries. Consequently, the invigoration of Indonesian government to all domestic universities to immediately program their institutions as the agents of economy development. Nonetheless, the implementation and management of Tri Dharma are not only specified on developing the strength of national economy but also on social conscience to make the current creativity and innovation can be more relevant to the need of subsistence resources development based on Indonesian characters and uniqueness driven by the moral sense of humanity, fairness and civilized policies. Therefore, the revitalization process should be accordingly manifested toward the principles of Tri Dharma of the university as mandated by Pancasila, Constitution of 1945, Law, GBHN and all of the derivative regulations, not strictly due to the insistence of global pressures. Thus, human resources must be the main agenda to revitalize among other potentials in generating and optimizing the ethic of scientific works in Tri Dharma activities in fulfilling the current necessitates without harming the interests of Indonesian populace. Finally, when Foreign Higher Education policies (FHE) are commercially inclined to globalize their education system and research which is relatively ‘capitalism’, thus our national higher education should be increasingly characterized by the humanity affectionate which elevates the dignity of Indonesia by providing serious devotions and concerns on social and community service.